Family support provided to children with autism spectrum disorder during COVID-19 pandemic - Al-Tal, Suhair Mamdouh; Al-Jawaldeh, Fuad Eid; Al-Taj, Heyam Musa; Aleid, Wafaa Ayed (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the level of family support provided to children with autism in light of the Covid 19 pandemic, and the Descriptive analytical method was adopted. To achieve the goals of this study, the researchers developed a tool that consisted of (29) items distributed into (3) dimensions (psychological, training, and recreational). The indications for the validity and reliability of this tool have been verified. The study sample included (86) mothers of children with autism spectrum disorder who were enrolled in special education centers for the year 2019/2020 in Amman, and the researchers reached many results, the most important of which are: The level of family support provided to children in light of the Covid 19 pandemic, according to their mothers' point of view, was average in the overall score of the Family Support Scale and in its three dimensions, where the mean of the total score was (3.34), and for the training dimension the mean was (3.51), while the recreational dimension was (3.41) and the psychological dimension was (3.12), the results indicated that there were no statistically significant differences at the level of significance (α = 0.05) in the level of family support provided to children with autism spectrum disorder in light of the Covid 19 pandemic according to the variables (economic status and educational qualification of mothers) and (age variable for children). The study recommended conducting more studies related to the impact of the Covid 19 pandemic on people with disabilities specifically for people with autism spectrum disorder, it also recommended to the relevant authorities the necessity to provide families and mothers of children with autism spectrum disorder with sufficient and necessary information about family support, its importance and the mechanism of its implementation
Keywords: Family support; children with autism spectrum disorder; Covid-19 pandemic